Evaluación del proceso de obtención de una biopelícula utilizando pectina extraída enzimáticamente de la cáscara de naranja valenciana (2019)
In the present investigation, the process of pectin extraction from the Valencian orange peel was evaluated, using the endo-polygalacturonase enzyme (Aspergillus niger), as an alternative to the acid hydrolysis process, for its subsequent application in the formulation of a biofilm. With the objective of evidencing the differences granted by the extraction method, in both cases it was used as raw material, dried and ground Valencian orange peel, with a particle size of 250 µm, likewise, precipitation was carried out, using ethanol at 70% and dried at room temperature. The extraction process by acid hydrolysis was carried out at 80 ° C, pH between 1.5-3 and constant stirring, for a time of 35 minutes. The enzymatic extraction process was carried out at an enzyme concentration of 200 ppm, 40 ° C, pH: 5.5 and constant stirring, for a period of 7 hours. There was a difference in yields between extraction methods of 5.32%.